Development of Equations to Predict Percentage Empty Body and Carcass Chemical Composition Adjusted for Breed Type and Sex in Growing/Finishing Cattle - Phillip A. Lancaster (Ruminants, 2025)
The estimation of body chemical composition is necessary to determine the nutrient requirements of growing/finishing cattle, but recent analyses indicate that published equations provide erroneous results when applied to diverse breed types and sexes. The objective of this analysis was to develop equations to estimate empty body and carcass chemical composition for different breed types and sexes. A dataset was developed from the published literature that contained 359 treatment means from 46 studies published between 1971 and 2021. Stepwise regression was used to develop prediction equations using Akaike’s Information Criteria to estimate empty body and carcass fat, protein, and ash concentrations (%). Empty body fat, protein, and ash could be predicted from combinations of empty body water, empty body fat, and empty body protein (RMSE = 1.53, 1.85, and 0.67; R2 = 0.99, 0.98, and 0.95). Breed type and sex affected the intercept and (or) slope coefficients to predict empty body fat, protein, and ash. Carcass fat, protein, and ash could be predicted from combinations of carcass water, carcass fat, and carcass protein (RMSE = 1.77, 1.62, and 0.82; R2 = 0.97, 0.98, and 0.93). Breed type and sex affected the intercept and (or) slope coefficients to predict protein and ash, but not fat. Equations adjusted for breed type and sex may be more robust than previously published equations based on a single breed or sex.